International banking standards in emerging markets: Testing the adaptation thesis in the European Union - Zdeněk Kudrna; Juraj Medzihorsky (Charles University in Prague, Institute of Economic Studies (IES), 2012)
This paper compares the bank regulatory regimes in the enlarged European Union in order to test the thesis claiming that international banking standards need to be adapted to emerging market circumstances. On the basis of World Bank surveys, we compile structural indices for the 10 post-communist EU members (emerging markets) as well as 17 advanced EU economies and compare them using Bayesian statistical procedures. Our findings show that there were systematic and significant differences, two-thirds of which can be explained by 8 of the 52 structural characteristics. The new member states regulatory regimes are more rule-based and leave less discretion for authorities, which is consistent with the thesis that the emerging market regulatory regimes - including those within the EU - needed to compensate for limited regulatory resources and higher political and economic volatility. Hence, the new generation of international banking standards should recognize these limitations.
Keywords: G21; K23; P51; 330; banking; emerging markets; European Union; international standards; regulation